2012
DOI: 10.1007/s11295-012-0579-3
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptome-based genetic map of Chinese chestnut (Castanea mollissima) and identification of regions of segmental homology with peach (Prunus persica)

Abstract: The Chinese chestnut (Castanea mollissima) carries resistance to Cryphonectria parasitica, the fungal pathogen inciting chestnut blight. The pathogen, introduced from Asia, devastated the American chestnut (Castanea dentata) throughout its native range early in the twentieth century. A highly informative genetic map of Chinese chestnut was constructed to extend genomic studies in the Fagaceae and to aid the introgression of Chinese chestnut blight resistance genes into American chestnut. Two mapping population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(136 citation statements)
references
References 63 publications
(68 reference statements)
5
129
2
Order By: Relevance
“…On the other hand, in the Px43 population analysis, each of the parental maps and the integrated map had 10 or 11 linkage groups. Using 145 Chinese chestnut SSRs developed by Kubisiak et al (2013) as anchor markers, we found that each linkage group in the new maps showed a one-to-one correspondence with one of the groups in the Chinese chestnut consensus map (Fig. S2).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…On the other hand, in the Px43 population analysis, each of the parental maps and the integrated map had 10 or 11 linkage groups. Using 145 Chinese chestnut SSRs developed by Kubisiak et al (2013) as anchor markers, we found that each linkage group in the new maps showed a one-to-one correspondence with one of the groups in the Chinese chestnut consensus map (Fig. S2).…”
Section: Discussionmentioning
confidence: 96%
“…A regression mapping algorithm was used to build the linkage maps, and map distances were calculated according to the Kosambi mapping function (Kosambi, 1944). The linkage group names were assigned according to the Chinese chestnut genetic linkage maps (Kubisiak et al, 2013). The genetic maps were drawn using MapChart v. 2.2 software (Voorrips, 2002).…”
Section: Construction Of Genetic Linkage Mapsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Owusu et al 2013). The PCR mix (15 µl) consisted of 6μl double deionized water (Ultra Pure Water, Molecular Grade from Phenix Research Products), 5μl HotFIREPol (Oak Biotechnologies, containing 2mM dNTPs, 1U Taq polymerase, 10mM MgCl 2 ), 0.2μl of 5 μM forward primer with M13 tail (5'-CA-CGACGTTGTAAACGAC-3'), 1.5μl of 5μM 5' dye labelled (6-FAM) M13 primer, 0.5μl of 5 μM pig-tailed (5'-GTTTCTT-3') reverse primer (Sigma Aldrich Inc., St. Louis, MO) (Schuelke 2000, Kubisiak et al 2013) and 2μl DNA (~ 2ng). The PCR touchdown reaction was performed in an Applied Biosystems 2720 Thermal Cycler (Foster City, CA) with the following cycling conditions: initial denaturation at 95 ºC for 15 minutes, 10 touch-down cycles of 1 minute at 94 ºC, 1 minute at 60 ºC (decreasing 1 ºC each cycle), and 1 minute at 72 ºC, followed by 25 cycles of 1 minute denaturation at 94 ºC, a 1 minute annealing step at 50 ºC, 1 minute elongation at 72 ºC, and a final extension at 72 ºC for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%